Mortgages and monetary policy - Carlos Garriga; Finn E. Kydland; Roman Šustek (Queen Mary University of London, School of Economics and Finance, 2015)
Mortgages are prime examples of long-term nominal loans. As a result, under incomplete asset markets, monetary policy can affect household decisions through the cost of new mortgage borrowing and the value of payments on outstanding debt. These channels are distinct from the transmission through real interest rates. A stylized general equilibrium model in corporating these features is developed. Persistent monetary policy shocks, resembling the level factor in the nominal yield curve, have larger real effects than transitory shocks. The transmission is stronger under adjustable- than fixed-rate mortgages. Higher, persistent, inflation benefits homeowners under FRMs but hurts them under ARMs.
Keywords: E32; E52; G21; R21; 330; Mortgages; Debt servicing costs; Monetary policy; Residential investment